1985
DOI: 10.1038/318533a0
|View full text |Cite
|
Sign up to set email alerts
|

The c-myc oncogene driven by immunoglobulin enhancers induces lymphoid malignancy in transgenic mice

Abstract: Transgenic mice bearing the cellular myc oncogene coupled to the immunoglobulin mu or kappa enhancer frequently develop a fatal lymphoma within a few months of birth. Since the tumours represent represent both immature and mature B lymphocytes, constitutive c-myc expression appears to be highly leukaemogenic at several stages of B-cell maturation. These myc mice should aid study of lymphoma development, B-cell ontogeny and immunoglobulin regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
1,315
10
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,665 publications
(1,381 citation statements)
references
References 53 publications
53
1,315
10
3
Order By: Relevance
“…This typical 'starry-sky' pattern was also seen in affected lymphoid organs of Em-myc; IL-7Ra þ /449F and Em-myc; IL-7Ra 449F animals in the majority of cases (data not shown; Figure 5a). In agreement with previous findings (Adams et al, 1985), Em-myc; IL-7Ra þ / þ tumors were composed of either pre-B or mature B cells, and this was also the case for the majority of the Em-myc; IL-7Ra 449F tumors (Supplementary Table 2). In addition, IL-7Ra 449F mutation did not affect the characteristic hyperproliferation induced by c-Myc in these end-stage tumors (data not shown).…”
Section: C-myc Tumors Retain Il-7 Responsiveness But Become Il-7 Indesupporting
confidence: 92%
See 2 more Smart Citations
“…This typical 'starry-sky' pattern was also seen in affected lymphoid organs of Em-myc; IL-7Ra þ /449F and Em-myc; IL-7Ra 449F animals in the majority of cases (data not shown; Figure 5a). In agreement with previous findings (Adams et al, 1985), Em-myc; IL-7Ra þ / þ tumors were composed of either pre-B or mature B cells, and this was also the case for the majority of the Em-myc; IL-7Ra 449F tumors (Supplementary Table 2). In addition, IL-7Ra 449F mutation did not affect the characteristic hyperproliferation induced by c-Myc in these end-stage tumors (data not shown).…”
Section: C-myc Tumors Retain Il-7 Responsiveness But Become Il-7 Indesupporting
confidence: 92%
“…This genetic analysis indicated that IL-7Ra signals involved in B lymphopoiesis were critical for the emergence of Em-myc-induced tumors. Overexpression of the c-Myc oncoprotein results in developmental arrest and pre-B-or B-cell lymphomas (Adams et al, 1985;Langdon et al, 1986). As IL-7Ra 449F mice have decreased numbers of peripheral B cells , it was possible the Em-myc; IL-7Ra 449F mice were protected from c-Myc-induced lymphomagenesis due to a decreased population of lymphoma precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MIF þ / þ p53 À/À (referred to as p53 À/À ) and MIF À/À p53 À/À (DKO) mice were derived from crosses between the double heterozygous animals. Wild-type, MIF À/À and p53 À/À mice (all 129Sv) were interbred with a C57Bl/6 strain of EmMyc transgenic mice 26,27 to obtain the F2 generations of MIF þ / þ , MIF þ /À , MIF À/À , and p53 þ /À transgenic animals. The genotype of mice was verified by PCR amplification specific for the corresponding Wild type (WT) and mutant alleles.…”
Section: Mice and Tissue Culturementioning
confidence: 99%
“…Vav‐BCL2 37, Vav‐Mcl1 31, and Eμ‐MYC 48 mice were described previously. Vav‐BFL1 and Vav‐BCLX TG mice were generated by pronuclear injection of the VavP vectors 36 encoding human FLAG‐BFL1 or human FLAG‐BCLX cDNA into C57BL/6N oocytes.…”
Section: Methodsmentioning
confidence: 99%